Establishing the Degree of Severity and the Mechanism of Fractures of the Metapacherous Bones of the Hand (Eurasian Medical Research Periodical, 2023)
Clarification of the criteria for establishing the severity of fractures of the metacarpal bones of the hand and determining the mechanism of their formation.